PERANCANGAN FILM DOKUMENTER SEBAGAI MEDIA KESADARAN BAHAYA BALAP LIAR DI KOTA MALANG - Marcelino Ferdy Kurniawan; Didit Prasetyo Nugroho; Aditya Nirwana (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2026)
The documentary film "GASPOL" was designed as a medium for raising awareness to address the phenomenon of illegal street racing in Malang City. This phenomenon is a complex social problem, driven by a lack of awareness among the younger generation about serious risks such as accidents, which in 2023 caused 148 serious injuries and material losses of Rp1.3 billion. The design methodology uses a descriptive qualitative approach through interviews, observation, and a literature review. Data was collected from various parties, including perpetrators, residents, and police. The result is a film with a strong expository narrative and a realistic visual style, designed to reveal the dangers, consequences, and solutions. The film aims to increase empathy and encourage positive behavioral change, making it an effective educational tool in the community.